A Review on Integration of Traditional and Modern Medicine (Asian Journal of Pharmaceutics (AJP), 2025)
Modern healthcare systems face several challenges in delivering comprehensive patient care, necessitatinginnovative approaches that combine traditional and contemporary medical practices. A synergistic integration oftraditional medicine systems, such as Ayurveda, Traditional Chinese Medicine, and indigenous healing practiceswith modern medical interventions offers promising solutions for enhanced healthcare delivery. Traditionalmedicine’s focuses on personalized care, preventive approaches, and holistic healing complements modernmedicine’s technological advancement and evidence-based methodologies. Integration studies demonstrateimproved patient outcomes in chronic disease management, particularly in diabetes, pain management, and mentalhealth conditions. The incorporation of traditional practices enhances cultural competence in healthcare deliverywhile addressing the diverse needs of global populations. Clinical evidence supports the efficacy of combinedtherapeutic approaches, such as acupuncture with conventional pain management and traditional herbal remedieswith modern pharmacotherapy. However, standardization of traditional practices, quality control measures, andregulatory frameworks remain critical challenges. Building effective partnerships between traditional healers andmodern healthcare professionals requires systematic approaches to overcome communication barriers and establishcommon ground. Present research validates traditional practices through scientific methods, strengthening thefoundation for integrated healthcare delivery. The development of standardized protocols, combined with rigoroussafety and efficacy assessments, paves the way for a more inclusive and effective global healthcare system thatrespects both traditional wisdom and modern medical advances.